Eksipien Koproses Pregelatinisasi Pati Singkong Metilselulosa sebagai Bahan Penyalut Tablet - Pradana, Rangga; Anwar, Effionora; Chaidir, Chaidir (Majalah Ilmu Kefarmasian, 2010)
Coating is one of the effective methods used in controlled release dosage form. Lots of variety in the form of a hydrophilic polymer excipient that is used to control the drug release many polymers that can be used for coating purposes, but only a few have been known to serve as a polymeric coating which functions to control the rate of drug release Pregelatinized cassava starch (PCS) is a physically modified starch. The purposes of the study were to improve functionality of PCS with making coprocess composed of PCS and methylcellulose (MC) by proportionally variation, which are 2:1, 3:1, and 4:1, as well as to applied co-processed excipient that could retard the drug release as coating material of theophylline tablet. Coprocessed excipient characterized in terms of morphology, particle size distribution, compressibility index, flow rate and angle of repose, thermal analysis, hygroscopicity, gel strength, swelling test, and moiety analysis.